Empowerment and Project Performance Success: The Role of Leadership and Power Distance - Caruajulca Mego, Percy Eduardo (Pontificia Universidad Católica del Perú, 2024)
The construction of infrastructure projects for extracting natural resources is vital to the economies of countries and the strategies of mining companies; their success or failures also affect the organizations and personnel involved. Project performance success (PJPF) means achieving the planned or approved scope, cost, schedule, and quality. This research aimed to analyze if PJPF is influenced by the team’s psychological empowerment (PEMP) and structural empowerment (SEMP), the project manager’s transformational leadership (TLD) and shared leadership (SLD) styles, and the cultural power distance (CPDT). The study examined the mediating roles as well of TLD and CPDT. Throughout a post-positivist epistemology, a quantitative paradigm, and a cross-sectional design in line with other project management studies, this paper tested its hypotheses using confirmatory factor analysis and structural equation modeling in AMOS. Data were collected using the online survey platform SurveyMonkey. Owners, contractors, and consultants from twenty-four countries across the Americas, Africa, Europe, Asia, and Australia contributed a total of 222 responses. All participants were involved in construction projects owned by a mining company listed in the S&P 500. PEMP has a positive impact on PJPF, SEMP, and CPDT. PEMP fosters engaged and autonomous employees with agility and problem-solving skills. TLD mediates the relationship between PEMP and SLD. The results indicated that SEMP, TLD, and SLD, on their own, do not directly contribute to project success. In contrast to prior studies, CPDT does not mediate the effects of PEMP on PJPF. The findings of this study offer guidance for all construction project stakeholders to improve their project success rates.

La construcción de proyectos de infraestructuras para la extracción de recursos naturales es vital para la economía de los países y las estrategias de las empresas mineras, su éxito o fracaso afecta a las organizaciones y el personal implicados. El éxito en el desempeño de un proyecto (PJPF) significa terminar según el alcance, costo, plazo y calidad previstos o aprobados. Esta investigación buscó analizar si el PJPF está influenciado por el empoderamiento psicológico (PEMP) y el empoderamiento estructural (SEMP) del equipo, los estilos de liderazgo transformacional (TLD) y de liderazgo compartido (SLD) del gerente del proyecto, y la distancia de poder cultural (CPDT). También se examinó el papel mediador del TLD y la CPDT. Bajo una epistemología post-positivista, un paradigma cuantitativo y un diseño transversal en línea con otras investigaciones en gestión de proyectos, este estudio puso a prueba sus hipótesis utilizando análisis factorial confirmatorio y modelo de ecuaciones estructurales en AMOS. Los datos se recopilaron mediante la plataforma SurveyMonkey. Propietarios, contratistas y consultores de veinticuatro países de América, África, Europa, Asia y Australia aportaron un total de 222 respuestas. Todos los participantes pertenecían al área de proyectos de construcción de una empresa minera listada en el S&P 500. El PEMP tiene un impacto positivo en el PJPF, el SEMP y la CPDT. El PEMP fomenta empleados comprometidos y autónomos con agilidad y capacidad para resolver problemas. El TLD media en la relación entre el PEMP y el SLD. Los resultados indican que SEMP, TLD y SLD, por sí solos, no contribuyen directamente al éxito del proyecto. En contraste con estudios anteriores, la CPDT no media los efectos de PEMP en PJPF. Las conclusiones de este estudio ofrecen una guía para que todos los interesados de los proyectos de construcción mejoren sus índices de éxito.
Keywords: Industria de la construcción--Administración; Construcción--Proyectos; https://purl.org/pe-repo/ocde/ford#5.02.04